Green Work Engagement Can Moderate The Effect Of Green Human Resource Management Variables On Employee Performance - Syech Idrus (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Abstract This research is quantitative research with an exploratory approach. The data used in this research is primary data that researchers obtained from distributing online questionnaires to 500 PTPN employees throughout Indonesia. The data obtained was analyzed using the smart PLS 4.0 analysis tool. The result in this article show the Green Human Resource Management variable can have a positive relationship and a significant influence on Employee Performance because the P-Values ​​value is below the minimum acceptance standard and the significant level is 0.05, namely 0.002. This is because environmental/green-based Human Resource Management in companies can make the environment comfortable, the quality of workers increases, costs related to potential environmental damage are reduced, and income remains stable. Apart from that, the second hypothesis in this research also shows the same thing if the Green Work Engagement variable can strengthen the influence of the Green Human Resource Management variable on employee performance because the P-Values ​​value is below the acceptable level and below the significance level. With employee involvement in HR management, the Company can create indicators or causes that explain the reasons why Green Human Resource Management variables can influence employee performance to become stronger. Thus the first and second hypotheses in this research can be accepted.